2007
DOI: 10.1007/s00441-007-0512-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel type of adherens junction in meningiomas and the derived cell line HBL-52

Abstract: Adhering junctions are generally grouped into desmosomes and adherens junctions based on their ultrastructural appearance and molecular composition. The armadillo-protein plakoglobin is common to both types of junctions, which are otherwise composed of mutually exclusive proteins. This view is based on observations in epithelial tissues but cannot easily be transferred to other cell types and tissues, as has become apparent during the last decade with the identification of new junctional proteins and the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…N-cadherin expression in tumor cells is regarded as a sign of invasive behavior. 1,9,12,27 Like E-cadherin, the N-cadherin molecule generally interacts with other N-cadherin molecules expressed in nearby cells in a homophilic manner. 26 Consequently, N-cadherin expressed on a tumor cell may increase its affinity for stromal cells, such as fibroblasts that normally express N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N-cadherin expression in tumor cells is regarded as a sign of invasive behavior. 1,9,12,27 Like E-cadherin, the N-cadherin molecule generally interacts with other N-cadherin molecules expressed in nearby cells in a homophilic manner. 26 Consequently, N-cadherin expressed on a tumor cell may increase its affinity for stromal cells, such as fibroblasts that normally express N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, invasive behaviors are a sign of progression. 1,9,12,27 Therefore, the mechanism by which canine meningiomas invade into the surrounding nervous tissue might be related to the expression of DCX and N-cadherin. The present study revealed the expression of a series of cell adhesion and related molecules in canine meningiomas by , moderate outliers; *, extreme outliers.…”
Section: Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arachnoid and the pia mater are lined with specialized epithelial cells called meningothelial cells. They are able to establish cell-cell junctions building a firm layer restricting the passage of cells or substances between the CSF and brain tissues or CSF and blood (2)(3)(4). Thus, meningothelial cells, along with endothelial cells of the blood-brain barrier, participate in isolating the central nervous system (CNS) from the rest of the body.…”
mentioning
confidence: 99%
“…It is expressed in normal arachnoid tissue, epithelial tissue and in human meningioma cells. The cytoplasmic tail of the E-cadherin molecules bind to -catenin to form the cadherin -actin filament complex, which is necessary for functional cell to cell adhesion [8,9]. Suppression of expression or cleavage of this adhesion molecule may result in cells acquiring a mesenchymal morphology and increased motility [10].…”
Section: Introductionmentioning
confidence: 99%